2017
DOI: 10.1371/journal.pone.0187814
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 is a proliferation and stem cell factor in hepatocellular carcinoma and possess widespread prognostic significance in different cancer types

Abstract: SOX9 has been previously shown to be involved in hepatocellular carcinoma (HCC) and other types of cancer. However, prognostic studies so far involved rather small cohorts or lack external validation and experimental data. In this study, we firstly determined the histological expression pattern of SOX9 in human HCC by immunohistochemistry (n = 84) and evaluated its prognostic value. External cohorts of publicly available datasets were used to validate its prognostic relevance in HCC (n = 359) and other types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
8
44
0
Order By: Relevance
“…We found that transcriptional factor Sox9 was a potential NBAT1-interacting candidate. As we know, Sox9 plays critical roles to drive cancer development including proliferation, migration, invasion, and angiogenesis [ 13–15 ]. RIP assay was used to confirm the interaction of between NBAT1 and Sox9 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…We found that transcriptional factor Sox9 was a potential NBAT1-interacting candidate. As we know, Sox9 plays critical roles to drive cancer development including proliferation, migration, invasion, and angiogenesis [ 13–15 ]. RIP assay was used to confirm the interaction of between NBAT1 and Sox9 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…33 Importantly, extended analysis in additional cohorts showed that those genes that were epigenetically changed by HCV infection and that persisted after DAA cure predicted HCC risk in cohorts of patients with HCV cirrhosis and SVR ( Figure 6C). Although we do not have experimental evidence that HCV-mediated modulation of SPHK1 or SOX9 gene expression is sufficient to promote cancer, our data combined with published knowledge on the role of these proteins in cancer biology 31,32 nevertheless suggest that SPHK1 and SOX9, among additional tumor-associated proteins, participate in HCV-induced HCC. This strongly supports the hypothesis that H3K27ac alterations of the identified genes precede HCC onset.…”
Section: Discussionmentioning
confidence: 54%
“…Results showed highly significant correlations in CA1a/AT for tumorigenic processes such as angiogenesis, cytokine-mediated signaling, cell migration, apoptosis and epithelial cell differentiation. Specific proteins in this group which have known roles in breast cancer include fibroblast growth factor receptor 2 (FGFR2) [ 11 ], filamin A (FLNA) [ 12 , 13 ], forkhead box A1 (FOXA1) [ 14 ], integrin subunit α5 (ITGA5) [ 15 ], intercellular adhesion molecule 1 (ICAM1) [ 16 ], interleukin 1β (IL1B) [ 17 ], interleukin 8 (CXCL8) [ 18 ], protein tyrosine kinase 6 (PTK6) [ 19 ], transcription factor SOX-9 [ 20 ], transforming growth factor β1 (TGFB1) [ 21 ], and Wnt-5a [ 22 ]. Please note that all three comparisons have significant associations for epithelial cell differentiation, but only the malignant CA1a cells within the CA1a/AT comparison is significantly associated with angiogenesis.…”
Section: Resultsmentioning
confidence: 99%